Moonshot : the flight of Apollo 11 - Floca, Brian (New York : Atheneum Books for Young Readers, 2009)
An illustrated account of the flight of Apollo 11 in 1969, the first manned mission to land on the moon.
"A Richard Jackson book.".
Includes bibliographical references and filmography.
Book Links (A.L.A.).
School Library Journal starred.
Wilson's Children.
Book Links (A.L.A.), January 2010.
Keywords: Apollo 11 (Spacecraft) -- Juvenile literature; Project Apollo (U.S.) -- Juvenile literature; Apollo 11 (Spacecraft); Project Apollo (U.S.); Apollo 11 (Spacecraft); Space flight to the moon -- Juvenile literature; Space flight to the moon; Apollo project; Space flight to the moon